Hydrotalcite Catalysts Prepared Using Combustion Method For Selective Etherification Of Glycerol To Diglycerol - Anuar, Mohd.Razealy (2013)
The concern on the depleting problem of petroleum diesel has encouraged many attempts to alternatively replace it with biodiesel fuel. Unfortunately, the enormous increase in the biodiesel production has mainly caused the surplus of glycerol production. Researches on utilizing and upgrading glycerol to value-added products should be promoted to stabilize the global market of glycerol. In the present study, glycerol was upgraded to diglycerol through a basic-catalyzed etherification reaction. The reaction was carried out in the presence of hydrotalcite as catalyst. Hydrotalcite was prepared using a combustion method. The hydrotalcite synthesis was studied by focusing on different experimental variables i.e. types of fuel used, calcinations temperatures, multi-anion source and amount of CO32- anion. For the etherification process, the catalytic activity of hydrotalcite was performed at the reaction temperatures between 200oC to 240oC in 16 h. The reaction kinetics was studied by varying the reaction temperature from 200oC to 260oC. The textural and chemical characteristics of the hydrotalcite were elucidated by means of X-ray diffraction for crystallinity, surface analysis for surface characteristics, Hammett indicator for basicity and basic strength, SEM for surface morphology and EDX for chemical composition. Glucose, fructose and saccharose were used as fuel and the calcination temperature were 450oC to 850oC. Glucose was identified as the most favourable fuel where the resulting catalyst was the most active with a conversion of 12.34 % and diglycerol selectivity of 97.73 % in 8 h.